Towards Central Bank Digital Currencies in Asia and the Pacific : Results of a Regional Survey - Jahan, Sarwat (FinTech Notes; FinTech Notes, 2022)
Drawing on survey responses from 34 Asian economies and country case studies, this note takes stock of recent developments related to central bank digital currencies (CBDCs) and crypto assets in Asia. The survey finds that there is significant heterogeneity in terms of stage of development, but the emergence of private crypto assets has created an impetus to consider CBDCs. While most countries are engaged in research and development, with some at advanced stages of testing and pilots, very few countries are likely to issue CBDCs in the near-to-medium term, reflecting the still considerable uncertainties. Still, country experiences so far provide some key insights for others in their journey in this area.